TRANSFUSI, SEL PUNCA, DAN TRANSPLANTASI ORGAN DALAM HUKUM KESEHATAN MASYARAKAT - Gunawan Widjaja; Mellisa Efiyanti (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
The regulation of transfusion, stem cells, and organ transplantation from a public health perspective in Indonesia has been supported by applicable laws and regulations. Meanwhile, problems related to the implementation of blood transfusions, stem cells, and organ transplants from the legal aspect of health in Indonesia, among others, during the Covid-19 pandemic, the availability of blood bag stocks was running low due to the PSBB factor in terms of Social Distancing so that blood donors who came did not meet their needs, including the provision of blood donations. convalescent plasma for Covid-19 patients with severe stages whose system is currently being drafted by the government.